2022
DOI: 10.3389/fmed.2022.902255
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection in Cirrhotic Patients With Portal Hypertensive Gastropathy: A New Enigma?

Abstract: The relationship between Helicobacter pylori (H. pylori) infection and Portal hypertensive gastropathy (PHG) is still a debatable matter. The aim of this study is to find out how common H. pylori infection is in cirrhotic patients with PHG and to see if there’s a link between H. pylori infection and PHG severity. Out of 340 cirrhotic patients who had upper Gastrointestinal Tract (GIT) endoscopy for early varices screening, 160 cirrhotic patients were selected and divided into 2 groups; 80 cirrhotic patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Portal hypertension produces changes in gastric mucosa, including alteration in vascular caliber, structure, and amount of blood flow. Helicobacter pylori , on the other hand, also alters gastric and duodenal microcirculation [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Portal hypertension produces changes in gastric mucosa, including alteration in vascular caliber, structure, and amount of blood flow. Helicobacter pylori , on the other hand, also alters gastric and duodenal microcirculation [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown an increased prevalence of H. pylori in portal hypertensive gastropathy; however, the true mechanism for this higher prevalence remains obscure, with different studies postulating different mechanisms. One of the popular theories is that H. pylori causes hypoxic mucosal surface and diminished epithelial integrity, which may facilitate colonization with this organism, while others claim that mucosal swelling and congestion, which increase nitric oxide, act as a suitable media for the growth of H. pylori [ 5 - 7 , 10 ]. Still, another famous theory is that in PHG, there is mucosal thinning and higher pH with decreased prostaglandin levels, facilitating H. pylori .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations